Association of systolic blood pressure levels with cardiovascular and cerebrovascular events and all-cause mortality: a result from the Kailuan study. Issue 3 (June 2016) - Song, Yuexia; Wu, Shouling; Liu, Xiaoxue; Qi, Xiaoyong
Abstract : Objective: We aimed to examine the impact of different levels of systolic blood pressure (SBP) on the incidence of cardiovascular and cerebrovascular events and all-cause death in Chinese adults. Patients and methods: A total of 97 013 Chinese men and women from the Kailuan study were followed up with the incidence of cardiovascular and cerebrovascular events and all-cause death. The participants were categorized into nine groups on the basis of the different SBP levels (mmHg) (groups 1–9): SBP<110, 110⩽SBP<120, 120⩽SBP<130, 130⩽SBP<140, 140⩽SBP<150, 150⩽SBP<160, 160⩽SBP<170, 170⩽SBP<180, and SBP≥180. Hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated from Cox regression models. Results: During a mean follow-up of 4.02 years, a total of 2043 cardiovascular and cerebrovascular events and 1686 of all-cause deaths occurred. After adjustments for potential confounding factors and using group 1 as a reference, HRs (95% CIs) of total cardiovascular and cerebrovascular events for groups 2–9 were 1.35 (1.00–1.82), 1.61 (1.22–2.12), 1.54 (1.16–2.04), 2.05 (1.55–2.72), 2.47 (1.86–3.29), 3.04 (2.28–4.06), 3.93 (2.89–5.36), and 4.56 (3.39–6.15), respectively. HRs (95% CIs) of all-cause death for groups 2–9 were 0.92 (0.71–1.20), 0.95 (0.75–1.20), 1.06 (0.83–1.34), 1.18 (0.93–1.50), 1.16 (0.90–1.49), 1.39 (1.07–1.81), 1.74 (1.29–2.33), and 2.06 (1.56–2.72), respectively. Conclusion: An increase in the SBP levels is significantly associated with an increased risk of cardiovascular and cerebrovascular events and all-cause death.